2015
DOI: 10.3233/jad-142037
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Uric Acid and Alzheimer's Disease in Elderly Jordanians

Abstract: The results suggest that serum UA levels are significantly lower in AD patients in comparison to control subjects. UA may have a protective role against AD; however this role needs further investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 40 publications
(42 reference statements)
3
28
0
1
Order By: Relevance
“…Uric acid in the PD model considerably attenuated the disease [139]. A study in AD patients also showed protective role of uric acid [140]. Exogenous administration of uric acid is also neuroprotective in experimental models of CNS diseases such as brain ischemia, meningitis, and ischemic stroke [138].…”
Section: Damage-associated Molecular Patternsmentioning
confidence: 99%
“…Uric acid in the PD model considerably attenuated the disease [139]. A study in AD patients also showed protective role of uric acid [140]. Exogenous administration of uric acid is also neuroprotective in experimental models of CNS diseases such as brain ischemia, meningitis, and ischemic stroke [138].…”
Section: Damage-associated Molecular Patternsmentioning
confidence: 99%
“…Of the remaining 35 studies, 6 studies were excluded for irrelevant outcomes and 5 studies were excluded for no usable data. Thus, 24 studies were finally included into the meta-analysis [14][15][16][17][18][19][20][21][22][23][24][28][29][30][31][32][33][34][35][36][37][38][39][40]. Among those 24 studies, 21 were case-control studies comparing serum uric acid levels in Alzheimer's disease patients with healthy controls [14-24, 28-32, 36-40] and 3 studies were cohort studies assessing risk of Alzheimer's disease in individuals with various categories of serum uric acid levels [33][34][35].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Among those 24 studies, 21 were case-control studies comparing serum uric acid levels in Alzheimer's disease patients with healthy controls [14-24, 28-32, 36-40] and 3 studies were cohort studies assessing risk of Alzheimer's disease in individuals with various categories of serum uric acid levels [33][34][35]. Among those 24 studies, 19 studies were published in English [14][15][16][17][18][19][20][21][22][23][24][28][29][30][31][32][33][34][35] while the other 5 studies were published in Chinese [36][37][38][39][40]. Those 21 case-control studies included a total of 1128 cases of Alzheimer's disease and 2498 controls without Alzheimer's disease [14-24, 28-32, 36-40].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, serum uric acid (UA) levels might be decreased in patients with Alzheimer's disease and Parkinsonism dementia (McFarland et al 2013;Al-khateeb et al 2015). A published meta-analysis in 2016 has reported a significant relationship between lower serum level of UA and development of Alzheimer's disease and Parkinsonism dementia (Khan et al 2016).…”
Section: Introductionmentioning
confidence: 99%